“SOLO” PRACTICE AS A CONSCIOUS CHOICE: THE DISCOURSE CONTENT - Yatsyna, Olena (PSYCHOLOGICAL JOURNAL, 2019)
The theme of “solo” practices is chosen due to the fact that modern civilizational development evokes such processes due to which social norms are losing / lost their unconditional significance and are ceasing / ceased to be relevant. That is why global social transformations influence semantic polyphony of practices; and this fact is legitimized by postmodernism. A peculiar answer to an individual’s reflexive understanding of social processes is appearance of the mosaic of practices used in “personal life-making”, in particular, “solo” practices, when loneliness is perceived as an adequate way of being in postmodern society. The phenomenon of loneliness is considered in the context of changing social-cultural conditions that activate searches for new content, new forms of organization of practices with an emphasis on individual, personal meanings. Given what has been written, the study of loneliness practices becomes an objective psychological problem of postmodern society and determines the importance of their essence revelation. The performed theoretical analysis allows us to distinguish two points of view on loneliness: the first one defines loneliness as a phenomenon that reflects a person’s internal disorder; the other point of view proclaims an ambivalent attitude towards loneliness: loneliness is determined as a tragedy, but, at the same time, it opens new possibilities for a person. The question is raised about the meaning of loneliness practices that is associated with the content of discourses, influencing agents’ corresponding behaviour. The research problem area is based on the postmodern principle of multi-variance; the essence and the features of the loneliness practices are determined, which allows us to outline transformational changes in the social reality. The article presents the qualitative analysis of the stories (auto-narratives) obtained by the interview method and the text data array obtained from Internet sources. The discourse-forming features of solo practices are determined. The conclusion is made about a conscious choice of “solo” meaning, when “solo” practices are perceived by agents as a resource for self-development, enjoyment of internal freedom and independence, everyday and psychological comfort. Owing to his/her special sensitivity / “tangible meaning”, an agent determines for him/herself the importance of the constructed practice meaning and coordinates the social world mosaic in relation to him/herself with individual meanings and many representations of him/herself, reinforcing the importance of self-creation and self-realization in the semantic polyphony of practices. The constructed “solo” practices indicate changes in the discourse on loneliness, which become an indicator of the semantic polyphony of practices so that the constructed practices correspond to actual life intentions of a person.